William Edgar Borah papers - Borah, William Edgar, 1865-1940.; Hileman, Grace
Correspondence, memoranda, speeches, articles, reports, notebooks, legislative files, subject files, patronage and constituent files, newspaper clippings, and other papers relating primarily to Borah's political interests and career in the U.S. Senate. Documents national politics and foreign and domestic policy during the period 1912-1940. Subjects include agriculture, antitrust legislation, constitutional interpretation, disarmament, foreign relations with the Soviet Union, isolationism, land utilization, the Lausanne treaty settlement, military activities in Latin America, League of Nations, neutrality legislation, New Deal and National Recovery Administration, Permanent Court of International Justice (World Court), the Red Scare, Franklin D. Roosevelt, Sino-Japanese War, U.S. Army affairs, universal military training, and outlawry of war. Other subjects include Idaho state politics and a 1936 attempt to secure Borah the Republican presidential nomination. Includes correspondence (1923-1936) of Borah's secretary, Grace Hileman.
Correspondents include Jane Addams, Edwin Borchard, Henry M. Dawes, Leonidas Carstarphen Dyer, Evan A. Evans, Hamilton Fish, James H. Gipson, Samuel Gompers, Frank Robert Gooding, Norman Hapgood, John W. Hart, James H. Hawley, Will H. Hays, John Haynes Holmes, James Weldon Johnson, Frank B. Kellogg, Frank Knox, Henry Cabot Lodge, Ray McKaig, Amos Pinchot, Gifford Pinchot, Raymond Robins, Irvin E. Rockwell, Franklin D. Roosevelt, Thomas Joseph Walsh, William Allen White, and Woodrow Wilson.
Lawyer and U.S. senator from Idaho.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Addams, Jane, -- 1860-1935 -- Correspondence; Borchard, Edwin, -- 1884-1951 -- Correspondence; Dawes, Henry M. -- 1877-1952 -- Correspondence; Dyer, Leonidas Carstarphen, -- 1871-1957 -- Correspondence; Evans, Evan A., -- 1876- -- Correspondence; Fish, Hamilton, -- 1849-1936 -- Correspondence; Gompers, Samuel, -- 1850-1924 -- Correspondence; Gooding, Frank Robert, -- 1859-1928 -- Correspondence; Hapgood, Norman, -- 1868-1937 -- Correspondence; Hart, John W., -- 1866-1935 -- Correspondence; Hawley, James H. -- 1847-1929 -- Correspondence; Hays, Will H. -- 1879-1954 -- Correspondence; Holmes, John Haynes, -- 1879-1964 -- Correspondence; Johnson, James Weldon, -- 1871-1938 -- Correspondence; Kellogg, Frank B. -- 1856-1937 -- Correspondence; Knox, Frank, -- 1874-1944 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; McKaig, Ray, -- 1880-1962 -- Correspondence; Pinchot, Amos, -- 1873-1944 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Robins, Raymond, -- 1873-1954 -- Correspondence; Rockwell, Irvin E. -- 1862-1952 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Walsh, Thomas Joseph, -- 1873-1952 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; League of Nations; Permanent Court of International Justice; Republican Party (U.S. : 1854- ); United States. -- Army; United States. -- Congress. -- Senate; United States. -- National Recovery Administration; Treaty of Lausanne -- (1923); Agriculture; Antitrust law; Communism -- United States; Constitutions -- United States; Constitutional law -- United States; Disarmament; Draft -- United States; Internal security -- United States; International cooperation; Isolationism -- United States; Land use -- United States; Neutrality -- United States; New Deal, 1933-1939.; Patronage, Political -- United States; Peace; Presidential candidates -- United States; Presidents -- United States -- Election -- 1936.; Sino-Japanese War, 1937-1945.; War; Idaho -- Politics and government; Latin America -- History, Military; Soviet Union -- Foreign relations -- United States; Turkey -- Foreign relations -- United States; United States -- Economic policy -- 1933-1945.; United States -- Foreign relations -- Soviet Union; United States -- Foreign relations -- Turkey